Influence of Family Circumstances, Peer Circumstances, and Entrepreneurial Learning on Entrepreneurial Interests with Self-Efficacy as Intervening Variables - Supandi, Riskan; Wulandari, Siti Zulaikha; Naufalin, Lina Rifda (Program Studi Pendidikan Ekonomi FKIP Universitas Lambung Mangkurat, 2022)
The research is a quantitative study aimed at knowing, analyzing, and testing the impact of family environment, peer environment, and entrepreneurship learning toward entrepreneurship interests with an self efficacy as an variable intervening of economics education student jenderal soedirman university.The data analysis techniques used are linear berganda regression analysis, test t and kausal step.This study suggests that: 1) The family environment affects the entrepreneurial interest of Student. 2) The peer environment affects directly the entrepreneurship interest of Student. 3) Entrepreneurship students directly affect the entrepreneurship interest of Student. 4) The family environment affect the self-efficacy of Student. 5) The peer environment affects the self-introduction of Student. 6) Entrepreneurship learning affect the self-efficacy of Student. 7) There is an indirect effect on entrepreneurship interests through the self-education of Student. 8) There is an indirect influence of peer education students through the development of Student. 9) There is a indirect impact of entrepreneurship education students through the absence of Student.